2021
DOI: 10.3390/atmos12030306
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Space Weather Events and the Incidence of Acute Myocardial Infarction and Deaths from Ischemic Heart Disease

Abstract: The effects of charged solar particles hitting the Earth’s magnetosphere are often harmful and can be dangerous to the human organism. The aim of this study was to analyze the associations of geomagnetic storms (GSs) and other space weather events (solar proton events (SPEs), solar flares (SFs), high-speed solar wind (HSSW), interplanetary coronal mass ejections (ICMEs) and stream interaction regions (SIRs)) with morbidity from acute myocardial infarction (AMI) and mortality from ischemic heart diseases (IHDs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 50 publications
0
11
0
1
Order By: Relevance
“…A number of studies have shown that reliable correlations between both LGMF [17] and GMF activity [18] and human organism functionalities are observed. While studies examining magnetic field disturbance show negative effects on health outcomes, a growing body of research is indicating that increases in the resonant frequencies in the Earth's magnetic fields is positively associated with the decrease of pathological processes.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that reliable correlations between both LGMF [17] and GMF activity [18] and human organism functionalities are observed. While studies examining magnetic field disturbance show negative effects on health outcomes, a growing body of research is indicating that increases in the resonant frequencies in the Earth's magnetic fields is positively associated with the decrease of pathological processes.…”
Section: Discussionmentioning
confidence: 99%
“…Vaičiulis et al . 2021). Namely, increases in the intensity of GCR‐particle flux have been suggested to increase overall deaths (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the impact of geomagnetic disturbances may depend on solar magnetic field polarity [22], the course and phase of the solar cycle, and on the strength of the exceptional solar events during the given period of observation [23][24][25][26][27][28]. The recent studies investigate also the simultaneous effects of space weather and meteorological situations on cardiovascular diseases [29][30][31][32], which can be important in the context of climate change.…”
Section: Introductionmentioning
confidence: 99%